Analisis Hukum terhadap Sanksi kepada Penyidik Kepolisian yang Tidak Segera Menyerahkan Berkas kepada Penuntut Umum dalam Perkara dengan Kualifikasi Ringan - Alfarobbi, Kevin Ariel; Ubaidillah, Lutfian U (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The Indonesian criminal justice system upholds the principle of legal certainty to ensure the protection of the rights of all parties involved in legal proceedings. One of the recurring issues is the ambiguity regarding the timeframe for Investigators to submit case files to Public Prosecutors, particularly in minor offense cases. Article 110 of the Indonesian Criminal Procedure Code (KUHAP) merely states the word "immediately" without specifying a definite time limit, creating opportunities for delays without firm legal consequences. This research employs a normative juridical method with a conceptual and evaluative approach to analyze statutory provisions and their practical application in Indonesia. The findings reveal that although ethical and disciplinary sanctions are regulated within internal police regulations, there is no explicit legal norm governing sanctions for Investigators who fail to promptly submit case files. Consequently, it is necessary to revise Article 110 of KUHAP by establishing a clear and binding timeframe, while strengthening both internal and external supervisory mechanisms to uphold legal certainty and enhance the effectiveness of the criminal justice system. Furthermore, public participation through digital media can serve as a form of social control over the negligence of law enforcement officers in Indonesia.